Structure and composition of arbuscular mycorrhizal fungal community associated with mango - Yang, Cuifeng; Teng, Zheng; Jin, Zhibo; Ouyang, Qiufei; Lv, Lingling; Hou, Xianbin; Hussain, Muzammil; Zhu, Zhengjie (Frontiers in Plant Science, 2025)
Mango (Mangifera indica L.) is an important fruit crop with significant economic value in tropical and subtropical areas globally. Arbuscular mycorrhizal fungal (AMF) symbiosis is vital for mango trees growth, and the detailed understanding of various (a)biotic factors that influence AMF community composition is crucial for sustainable crop production. To date, there is little information available on how do different seasons and plant age influence the AMF community composition associated with mango. Using high-throughput amplicon sequencing, we examined AMF community diversity and composition in the rhizosphere of mango from two distinct orchards during spring (C_BY and C_YL) and autumn (Q_BY and Q_YL), which differed in age (10 and 28 years). The results revealed a notable variation in the number of observed species between two 28-years-old mango orchards (C_BY28 vs C_YL28 and Q_BY28 vs Q_YL28) during both the spring and autumn seasons. However, the comparison of 10-years-old and 28-years-old mangoes showed no significant shift in the diversity and richness of AMF. At the taxonomic level, Glomus was the absolute dominant genus in AMF community. The correlation analysis between species abundance and soil nutrients showed that the level of phosphorus, potassium and their available forms (AP, AK) significantly affect AMF community. Furthermore, the P, AP, and AK contents were found positively correlated with the dominant AMF molecular virtual species Sclerocystis sinuosa. These findings indicate the response characteristics of mango rhizosphere AMF community to soil nutrients, providing scientific basis for precise regulation of soil environment to improve mango tree growth and production.